Dynamic Recrystallization Can Produce Porosity in Shear Zones. Issue 7 (6th April 2020) - Gilgannon, James; Poulet, Thomas; Berger, Alfons; Barnhoorn, Auke; Herwegh, Marco
Abstract: Creep cavities are increasingly recognized as an important syn‐kinematic feature of shear zones, but much about this porosity needs investigation. Largely, observations of creep cavities are restricted to very fine grained mature ultramylonites, and it is unclear when they developed during deformation. Specifically, a question that needs testing is should grain size reduction during deformation produce creep cavities? To this end, we have reanalyzed the microstructure of a large shear strain laboratory experiment that captures grain size change by dynamic recrystallization during mylonitization. We find that the experiment does contain creep cavities. Using a combination of scanning electron microscopy and spatial point statistics, we show that creep cavities emerge with, and because of, subgrain rotation recrystallization during ultramylonite formation. As dynamic recrystallization is ubiquitous in natural shear zones, this observation has important implications for the interpretation of concepts such as the Goetze criterion, paleopiezometery, and phase mixing. Plain Language Summary: At great depths inside the Earth, rocks called mylonites slowly deform and accommodate tectonic forces. Generally, these rocks are considered to have no porosity because the pressure they experience is very large. However, it is frequently documented that these mylonites focus the transport of mass, both fluid and solid, through the crust. This implies that mylonites host a permeable porosity. To better understand this paradox, we reanalyzed an old laboratory experiment that documented the formation of a mylonite. We showed that a porosity, known as creep cavities, forms synchronously with the mylonite. This is an important experimental finding because it suggests that creep cavities are a fundamental feature of mylonites. Our results showcase a rare snapshot into the dynamics of rocks important for tectonics and advance larger questions about their transport properties. Key Points: Creep cavities emerge with grain size reduction by subgrain rotation recrystallization Porosity driven by creep can be opened and sustained at high confining pressures There is a direct and spontaneous physical path for single‐phase rocks to transition to polyphase rocks during deformation